Personal private herbaria: a valuable but neglected source of floristic data. The case of Italian collections today - Francesco Roma-Marzio; Lorenzo Peruzzi; Gianni Bedini (Italian Botanist, 2017)
Today private collections still represent an important source of information as is evident from the available literature, where, in many cases, private collections are mentioned both in floristic and taxonomic/systematic researches. We present a summary of the main information about private herbaria in Italy, whose collections are currently increasing. Based on our survey, we retrieved information on 34 personal herbaria where 156,361 specimens are preserved at present. Piedmont and Tuscany resulted the two Italian regions with the highest number of collections, whereas for 9 regions we obtained no answer. The most represented families resulted Asteraceae and Poaceae, whereas the most represented genera resulted Carex, Trifolium, and Hieracium. Taken all together, these collections rank 16th among the 68 institutional public herbaria officially recognised in Italy.